Pediatric circumcision using n‐butyl‐cyanoacrylate plus MS monomer: Bacteriostatic and cosmetic advantages over suture. Issue 4 (6th December 2020) - Spinelli, Claudio; Bertocchini, Alessia; Leoni, Matteo; Calani, Chiara; Morganti, Riccardo; Strambi, Silvia
Abstract: Purpose: The aim of this study is to compare the use of n‐butyl‐cyanoacrylate plus MS monomer (NBCA‐MS) glue with suture in pediatric circumcision. Materials and Methods: Between January 2013 and January 2017, 160 consecutive pediatric patients (range 18 months–14 years, mean 7.5 years) underwent circumcision. Eighty patients were randomly allocated to the glue group and 80 to the suture group. In the glue group wound margins were approximated by n‐butyl‐cyanoacrylate plus MS monomer (NBCA‐MS) glue while in the suture group interrupted 5‐0 polyglycolic acid stitches were used. Each group was randomized into two subgroups: forty patients (subgroup A) received antibiotics (6 days of amoxicillin/clavulanic acid) and 40 (subgroup B) patients did not receive any postoperative drug. Operative time, pain score, postoperative complications and cosmesis were statistically evaluated. Results: The operation time was significantly higher in the suture group; pain severity and duration were not significantly lower in the glue group. In the 80 patients of the glue group no complications occurred; in the suture group 20 (25%) cases of wound edema and 6 (7.5%) infections occurred. Cosmesis evaluation 1 and 6 months postoperatively showed significantly better results in the glue group. Conclusion: Our study demonstrates that NBCA‐MS glue wound closure in pediatric circumcision is a safe and effective technique.